Who Wants To Share? Attitudes Towards Horizontal Redistribution Across the Globe - Stewart, Frances (2024)
While recent literature has extensively addressed inequalities between households or individuals, known as “vertical inequalities,” there remains a dearth of research on socio‐economic disparities among culturally defined groups, termed “horizontal inequalities” (HIs). In diverse societies, addressing such group disparities is imperative to promote economic efficiency, political stability, and social cohesion. This thematic issue investigates the level of public support for HI‐correcting policies across nine contexts: Brazil, South Africa, Nigeria, Malaysia, Kenya, Western Balkans, India, the United States, and Northern Ireland. The articles within this issue collectively identify and analyze crucial factors at the individual, group, and national levels. In this editorial, we summarize major findings, reflecting on the salience of group identity across majority and minority contexts, the role of perceptions vs more objective measures of inequality and its causes, and the significance of shifting political climates and societal discourses.